Operative vaginal delivery over a 5-year period (2000-2004) at the San Vicente de Paúl teaching hospital in Medellín, Colombia Parto vaginal instrumentado en el Hospital Universitario San Vicente de Paúl durante un periodo de 5 años (2000-2004), Medellín, Colombia - Hernán Cortés; Eugenio Escobar (Federación Colombiana de Obstetricia y Ginecología, 2006)
Objective: Determining the percentage of operative vaginal deliveries at the San Vicente de Paúl teaching hospital over a five-year period and characterising operative deliveries in relation to the type of forceps, indications, and techniques used. Methods: Descriptive retrospective study carried out at the hospital 2000-2004, including all deliveries during this period. Results: 9,255 deliveries were included; 2% (185) of them were operative vaginal deliveries. Kielland forceps were those most used, 63% being outlet and low forceps. Nineteen percent of patients suffered grade III and IV perineal tears. Conclusions: A low incidence of operative vaginal deliveries was observed; this is decreasing. The incidence of tears was low in relation to other series. The teaching and practice of the art of using forceps should be encouraged. Objetivo: determinar el porcentaje de partos instrumentados en el Hospital Universitario San Vicente de Paúl, durante un periodo de 5 años y caracterizar los partos en relación al tipo de fórceps utilizados, indicaciones y técnica empleada. Materiales y Métodos: estudio descriptivo retrospectivo, realizado en el Hospital Universitario San Vicente de Paúl del 2000 - 2004, donde se incluyeron todos los partos atendidos en este periodo. Resultados: se atendieron 9.255 partos, de los cuales el 2% (185), fueron instrumentados con fórceps. El fórceps más usado fue el de Kielland y el 63% fueron fórceps bajos y de desprendimiento. Se presentaron desgarros grados III y IV en el 19% de las pacientes sometidas a parto instrumentado. Conclusiones: se presentó una incidencia baja de parto instrumentado y está disminuyendo, la incidencia de desgarros fue baja en relación con otras series. Se debe estimular la enseñanza y práctica del arte de los fórceps.